2021
DOI: 10.1016/j.resuscitation.2021.03.034
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on the Australian public’s willingness to perform hands-only CPR

Abstract: To the Editor,The provision of bystander CPR in public places relies on the public's willingness to intervene and provide first aid to a stranger. Recent surveys suggest approximately half of members of the public are willing to provide CPR to a stranger, 1 with fear of infection rarely reported as a barrier. 1,2 However, this may have changed in the current era of the highly infectious COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“… [16] , [17] A large survey conducted by Grunau et al showed that there was a significant decrease in willingness to provide CPR during the early pandemic, 18 while an Australian survey conducted by Howell et al suggested that the public’s willingness to perform bystander CPR did not change at the peak of the pandemic. 19 So far there has been no study exploring the impact of the pandemic on the incidence of OHCA and bystander CPR in HK, where the survival rate of OHCA was previously found to be 2.3%, while the neurologically favourable survival rate was 1.5%; [20] , [21] bystander CPR was performed in 28.8% of cases. [20] , [21] As the pandemic continues, it is imperative to review local data and assess the trend in incidence of OHCA, bystander CPR and survival outcome, which is invaluable to optimise local OHCA care, as it is highly probable that COVID-19 will linger on for a prolonged period or become an endemic.…”
Section: Introductionmentioning
confidence: 99%
“… [16] , [17] A large survey conducted by Grunau et al showed that there was a significant decrease in willingness to provide CPR during the early pandemic, 18 while an Australian survey conducted by Howell et al suggested that the public’s willingness to perform bystander CPR did not change at the peak of the pandemic. 19 So far there has been no study exploring the impact of the pandemic on the incidence of OHCA and bystander CPR in HK, where the survival rate of OHCA was previously found to be 2.3%, while the neurologically favourable survival rate was 1.5%; [20] , [21] bystander CPR was performed in 28.8% of cases. [20] , [21] As the pandemic continues, it is imperative to review local data and assess the trend in incidence of OHCA, bystander CPR and survival outcome, which is invaluable to optimise local OHCA care, as it is highly probable that COVID-19 will linger on for a prolonged period or become an endemic.…”
Section: Introductionmentioning
confidence: 99%
“…Our work complements data from other regions where the willingness of bystanders to provide CPR did not waver during the COVID-19 pandemic. [3] , [20] , [21] , [22] …”
Section: Discussionmentioning
confidence: 99%
“…Teaching only ECCs in CPR to the population was justified, until January 2020, as an acceptable method to increase the number of OHCAs served by the population [ 4 , 5 , 10 , 19 , 27 , 31 ]. In the current socio-sanitary framework, with serious risk of abandonment of assistance to victims in cardiac arrest in domestic, work, and social environments, the “Salvando a Llanetes ® ” device, by achieving a high percentage of correct ECCs, is suitable for citizens to learn CPR in large training groups [ 5 , 6 , 22 ]. As a device that bases training on the “CPR Hands-Only™” method, it is safe against the transmission of diseases, including COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Organizations such as the International Liaison Committee (ILCOR), the American Heart Association (AHA) and the European Resuscitation Council (ERC) advocate for simplification and universality of basic CPR; for this purpose, they have implemented plans like “CPR Hands-Only™” [ 4 , 5 ]. In addition, the ongoing COVID-19 pandemic has changed resuscitation workflows, mainly influenced by risks of contamination during mouth-to-mouth ventilation [ 6 , 7 ]. Consequently, current guidelines recommend the rapid application of chest compressions up until the arrival of emergency medical services (EMS) personnel [ 8 ].…”
Section: Introductionmentioning
confidence: 99%